Correction note. - Pace, Roberto (Contributions to Entomology = Beiträge zur Entomologie, 2013)
I thank Dr. Eckhard Groll, entomology information center and editor of „Contributions to Entomology - Beiträge zur Entomologie“ Muencheberg, Germany, for drawing my attention to a secondary homonym and propose hereby the following new name: Trichoglossina grolli nomen novum for Trichoglossina tronqueti Pace, 2012: 148 and not Trichoglossina tronqueti (Pace, 1987), formerly Hygropetrophila tronqueti Pace, 1987: 417; Pace, 2012: 143.Nomenclatural Actsgrolli Pace, 2013 (Trichoglossina), nom. n. pro Trichoglossina tronqueti Pace, 2012, nec Pace 1987